2015
DOI: 10.1016/j.immuni.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell Reprogramming toward a Th2-Cell-like Lineage Impairs Oral Tolerance and Promotes Food Allergy

Abstract: Summary Oral immunotherapy has had limited success in establishing tolerance in food allergy, reflecting failure to elicit an effective regulatory T (Treg) cell response. We show that disease-susceptible mice (Il4raF709) with enhanced IL-4 receptor (IL-4R) signaling exhibited STAT6-dependent impaired generation and function of mucosal allergen-specific Treg cells. This failure was associated with the acquisition by Treg cells of T helper 2 (Th2) cell-like phenotype, also found in peripheral blood allergen-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
228
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(246 citation statements)
references
References 50 publications
14
228
2
2
Order By: Relevance
“…7, 8 Other studies also suggest that Treg cells are involved in controlling the development and resolution of allergic diseases. 913 Accordingly, the balance between the activation of Th2-type immunity and the regulatory activity of Treg cells may play a pivotal role in the evolution of allergic airway diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 8 Other studies also suggest that Treg cells are involved in controlling the development and resolution of allergic diseases. 913 Accordingly, the balance between the activation of Th2-type immunity and the regulatory activity of Treg cells may play a pivotal role in the evolution of allergic airway diseases.…”
Section: Introductionmentioning
confidence: 99%
“…29 More recently, “Th2 cell-like” Treg cells have been identified in the intestine and secondary lymphoid organs in a mouse model of food allergy involving a gain-of-function IL-4Rα chain allele. 9 In humans, Treg cells that express type 2 cytokines, such as IL-4 and IL-13, were detected in the skin of patients with systemic sclerosis. 30 Thus, Treg cells are likely altered when influenced by certain tissue microenvironments.…”
Section: Introductionmentioning
confidence: 99%
“…Oral anaphylaxis is hard to achieve in most mouse models; therefore different challenge strategies are used, and systemic anaphylaxis is commonly monitored as the readout. In mice, the decrease in core body temperature after systemic, cutaneous, or intragastric allergen challenges is monitored by rectal or subcutaneous probes 35, 36. In addition, allergic diarrhea can be scored by assessing the stool viscosity and stool hemorrhage, and they have been used as another readout for intestinal anaphylactic responses.…”
Section: Pathophysiology Of Human Food Allergy As Reflected In Murinementioning
confidence: 99%
“…It can therefore be concluded that constitutive activation of the IL4Rα can circumvent the tolerance pathways by providing the IL4R signaling achieved in other models with adjuvants such as cholera toxin 57 . Allergic patients fail to develop oral tolerance to their allergen in part because of a defect in the generation of Tregs, which are not only vital to tolerance of the adaptive immune system but have been shown to have a direct effect on mast cells by blocking degranulation 35, 58, 59, 60. The IL4RF709 mice can reproduce this absence to produce allergen-specific Tregs 35 .…”
Section: Adjuvant-free Oral Sensitization or Spontaneous Sensitizatiomentioning
confidence: 99%
“…IL-4 receptor signaling has been shown to impair the capacity of Tregs to suppress mast cell activation and expansion, which in turn drives Th2-cell reprogramming of Tregs [39] . Moreover, IL-4 inhibits mouse CD5 + B1 cells from adopting a macrophage-like morphology [38] .…”
Section: Foxp3mentioning
confidence: 99%